2021
DOI: 10.1096/fasebj.2021.35.s1.03869
|View full text |Cite
|
Sign up to set email alerts
|

Functional Changes to the Modulation of α4β2* Nicotinic Acetylcholine Receptors during Postnatal Maturation

Abstract: The neurotransmitter acetylcholine (ACh) acting at its α4β2* subtype of nicotinic acetylcholine receptor (nAChR) within the cerebral cortex plays an important role to support cognitive functions. ACh normally initiates a robust excitatory response at α4β2* nAChRs, although this activity may be modulated by a number of mechanisms that alter receptor function. Negative receptor modulation may occur via desensitization by the competitive agonist nicotine or via presumed negative allosteric modulation by the endog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 115 publications
0
4
0
Order By: Relevance
“…Moreover, P4 is regarded as an allosteric modulator of the nAchR 16 . An experimental study found that P4 activates central nAchR leading to neuroprotective effects 113 .…”
Section: Human Immune Deficiency Virus 1 (Hiv‐1)mentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, P4 is regarded as an allosteric modulator of the nAchR 16 . An experimental study found that P4 activates central nAchR leading to neuroprotective effects 113 .…”
Section: Human Immune Deficiency Virus 1 (Hiv‐1)mentioning
confidence: 99%
“…Moreover, P4 is regarded as an allosteric modulator of the nAchR. 16 An experimental study found that P4 activates central nAchR leading to neuroprotective effects. 113 In COVID‐19, SARS‐CoV‐2 binds nAchR leading to dysregulation of the anti‐inflammatory cholinergic system with further augmentation of the release of pro‐inflammatory cytokines.…”
Section: Human Immune Deficiency Virus 1 (Hiv‐1)mentioning
confidence: 99%
See 2 more Smart Citations